Pepsee systems: grassroots innovation under groundwater stress - Verma, Shilp; Tsephal, S.; Jose, T. (2004)
Drip irrigation, in its various forms, is the dominant mode of micro-irrigation in India. The benefits of these technologies in water scarce regions have been widely studied all over the world. A review of literature on drip-irrigation technologies strongly suggests that there are significant financial, economic and social benefits in the adoption of these technolgoies. In the Maikaal region of Central India, a grassroots innovation called 'Pepsee' has become a popular choice for farmers. At less than half the cost of conventional drip systems, this innovation promises comparable returns. What is most interesting is that while government and non-government agencies have struggled to promote water-saving technologies across the country, the people in this area have adapted and adopted these technologies on their own. This paper looks at the various aspects of this grassroots innovation, its spread, adoption behavior and impacts. The authors find that while Pepsee and other water-saving technolgoies do lead to farm level improvements in water efficiency, they will not contribute to system level 'real' water saving unless a favorable policy environment encourages their adoptin on a large scale.